Membangun Kepercayaan Masyarakat Terhadap Bank Syariah: Sebuah Tinjauan Literatur Tentang Strategi dan Tantangan - Frandika Situmorang; Eza Syahbana; Jeane Alisya; Hasyim Hasyim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the era of globalization and modern economic development, the Islamic banking industry has become one of the fastest growing sectors in Indonesia. Nevertheless, there are still challenges in building public trust in the Islamic banking system. This article aims to review the literature related to strategies and challenges in building public trust in Islamic banks. Through a comprehensive literature review, this article explores the factors that influence public trust, such as sharia principles, transparency, and quality services. In addition, the article also analyses the challenges faced by Islamic banks, such as public perception, lack of understanding, and competition with conventional banks. By identifying existing strategies and challenges, this article provides valuable insights for the Islamic banking industry, academics, and policymakers in an effort to increase public trust and foster sustainable growth within the sector.